Low-dose PCB126 exposure disrupts cardiac metabolism and causes hypertrophy and fibrosis in mice. (1st December 2021) - Wang, Can; Cui, Ruina; Niu, Congying; Zhong, Xiali; Zhu, Qicheng; Ji, Di; Li, Xianjie; Zhang, Hongxia; Liu, Chunqiao; Zhou, Lina; Li, Yanli; Xu, Guowang; et al.
Abstract: The residue of polychlorinated biphenyls (PCBs) exists throughout the environment and humans are subject to long-term exposure. As such, the potential environmental and health risk caused by low-dose exposure to PCBs has attracted much attention. 3, 3′, 4, 4′, 5-pentachlorobiphenyl (PCB126), the highest toxicity compound among dioxin-like-PCBs, has been widely used and mass-produced. Cardiotoxicity is PCB126's crucial adverse effect. Maintaining proper metabolism underlies heart health, whereas the impact of PCB126 exposure on cardiac metabolic patterns has yet to be elucidated. In this study, we administered 0.5 and 50 μg/kg bw of PCB126 to adult male mice weekly by gavage for eight weeks. Pathological results showed that low-dose PCB126 exposure induced heart injury. Metabolomic analysis of the heart tissue exposed to low-dose PCB126 identified 59 differential metabolites that were involved in lipid metabolism, amino acid metabolism, and the tricarboxylic acid (TCA) cycle. Typical metabolomic characteristic of cardiac hypertrophy was reflected by accumulation of fatty acids (e.g. palmitic, palmitoleic, and linoleic acid), and disturbance of carbohydrates including D-glucose and intermediates in TCA cycle (fumaric, succinic, and citric acid). Low-dose PCB126 exposure increased glycine and threonine, the amino acids necessary for the productions of collagen and elastin. Besides, PCB126-exposed mice exhibited upregulation of collagen synthesis enzymes and extracellular matrix proteins, indicative of cardiac fibrosis. Moreover, the expression of genes related to TGFβ/PPARγ/MMP-2 signaling pathway was perturbed in the PCB126-treated hearts. Together, our results reveal that low-dose PCB126 exposure disrupts cardiac metabolism correlated with hypertrophy and fibrosis. This study sheds light on the underlying mechanism of PCBs' cardiotoxicity and identifies potential sensitive biomarkers for environmental monitoring. Graphical abstract: Image 1 Highlights: Exposure to the environmentally relevant level of PCB126 leads to heart injury in adult male mice. PCB126 exposure disrupts cardiac metabolism related to fatty acids, TCA cycle and amino acids. The cardiac metabolomic feature manifests cardiac hypertrophy and fibrosis.